Caracterização por espectroscopia de fotoelétrons de nanotubos de carbono funcionalizados - Jordana Aparecida Gravito Rodrigues (2011)
This work deals with the characterization of functionalized carbon nanotubes, using photoelectron spectroscopy (XPS). The nanotubes are multi-walled nanotubes (MWNT) grown by chemical vapor deposition (CVD) and single-walled nanotubes (SWNT) grown by electric arc discharge. By functionalization we mean the aggregation of functional groups to the walls of the nanotubes. Functionalization of nanotubes is important in order to turn them more interesting for practical applications, since non-functionalized nanotubes are non-polar materials, i.e., they do not dissolve in water. The performed functionalization was of the covalently type, using H2SO4 (SWNT) and HNO3 (MWNT) acids, with the aid of a microwave oven, which reduces the reaction time. From the SWNT samples the most efficient functionalization occurred in 20 minutes of processing time, while for the MWNT, 20 and 30 minutes of reaction were the most effective. For shorter times of processing the functionalization is less effective, and for longer times probably the acids degrade the nanotubes. For the investigation and characterization of the functionalized nanotubes, in addition to the XPS technique, we also used transmission electronic microscopy (TEM), scanning electronic microscopy (SEM) and Raman spectroscopy. What we observe is that photoelectron spectroscopy, being extremely surface sensitive, was the most successful technique to characterize the process and efficiency of the functionalization